2020
DOI: 10.3390/molecules26010044
|View full text |Cite
|
Sign up to set email alerts
|

Two New Aristolochic Acid Analogues from the Roots of Aristolochia contorta with Significant Cytotoxic Activity

Abstract: Twelve compounds, including two new aristolochic acid analogues with a formyloxy moiety (9–10) and 10 known aristolochic acid derivates (1–8 and 11–12), were obtained from the roots of Aristolochiacontorta. Their structures were elucidated using extensive spectroscopic methods. Their cytotoxic activity in human proximal tubular cells HK-2 was evaluated by the MTT method, which has been widely used to assess cell viability. Among these molecules, compounds 3 and 9 were found to be more cytotoxic. Furthermore, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…AA and its derivatives cause nephrotoxicity and urinary tract tumors, an effect that has been widely recognized in the past few decades. 23 , 48 It has also been reported that long-term use of AAs-containing herbal remedies has been linked to tumors in multiple organs, including kidney, stomach, bladder, and subcutaneous tumors. 11 Although herbal preparations containing AAs have been phased out in multiple countries such as Japan, Canada, the UK, the USA, Australia, and Europe, 5 , 49 there are still some regions in which people are exposed to AAs by inadvertently taking certain herbal medicines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AA and its derivatives cause nephrotoxicity and urinary tract tumors, an effect that has been widely recognized in the past few decades. 23 , 48 It has also been reported that long-term use of AAs-containing herbal remedies has been linked to tumors in multiple organs, including kidney, stomach, bladder, and subcutaneous tumors. 11 Although herbal preparations containing AAs have been phased out in multiple countries such as Japan, Canada, the UK, the USA, Australia, and Europe, 5 , 49 there are still some regions in which people are exposed to AAs by inadvertently taking certain herbal medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, microenvironmental alterations associated with carcinogenesis due to AAI inducing A→T transversions will be needed. Thirdly, under the conditions of long-term induction of liver cancer by AAI and the presence of A→T transversions and AAI–DNA adducts, 20 , 23 it is urgent to dissect the development of liver carcinogenesis by single-cell sequencing and multi-omics combined analysis strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The content of aristolochic acid (AA)-I in AR was limited to 0.001% by the Chinese pharmacopoeia in 2005. However, recent studies have shown that AAs such as AA-II, AA-III, AA-IVa, AA-VIIa, and aristololactam I (AL-I) possibly existing in AR [ 11 , 12 ] are also cytotoxic to renal tubular epithelial cells as AA-I more or less [ 13 16 ]. The standards of pharmacopoeia may neglect the toxicity of AAs other than AA-I.…”
Section: Introductionmentioning
confidence: 99%
“…This kidney disease was first detected in Belgium in 1992, and since then, cases have been detected all over the world, eventually being defined as aristolochic acid nephropathy (AAN) [ 11 , 12 ]. Numerous data have shown that AA-containing plants and their derivatives are nephrotoxic, mutagenic, and carcinogenic to humans [ 2 , 13 , 14 ]. The International Agency for Research on Cancer (IARC) has classified AAs and the plants that contain them as Group I carcinogens [ 15 ].…”
Section: Introductionmentioning
confidence: 99%